Primary squamous cell carcinoma kidney: A rare case report - Vijay Domblae; Shivanand Gundalli; MH Prabhu; Singhania Somil; Sonali (Our Dermatology Online, 2016)
Primary squamous cell carcinoma (SCC) of the kidney is a very rare clinical entity. Only a few cases have been reported in world literature. Here we report a case with renal SCC. The patient presented with flank pain, fever and vomiting. In ultrasonography, renal mass was detected and after nephrectomy followed by histopathological examination, it was diagnosed as SCC. It was associated with renal calculi and hydronephrosis. The lack of characteristic presentation like hematuria, pain and palpable mass causes delay in diagnosis results in locally advanced or metastatic disease at presentation.